Sodium Butyrate Supplementation: Current Evidence, Clinical Indications, and Limitations - Michalak, Karolina; Fahim, Knieszko; Franaszek, Jakub; Herchi, Nadia; Jabrzyk, Martyna; Jarczyńska, Patrycja; Kijowski, Wojciech; Klusek, Mateusz; Przybył, Maciej (Quality in Sport, 2026)
Introduction and purpose: Butyrate is one of the most important short-chain fatty acids produced by the gut microbiota through fermentation of undigested dietary components, especially dietary fiber. It plays a key role in intestinal homeostasis by supporting colonocyte metabolism, maintaining epithelial barrier integrity, and modulating immune responses. The aim of this paper was to review current evidence on sodium butyrate supplementation, with particular attention to its mechanisms of action, clinical indications, and limitations of the available evidence. A brief description of the state of knowledge: Experimental studies suggest that butyrate exerts anti-inflammatory, immunomodulatory, and barrier-protective effects. Its mechanisms include histone deacetylase inhibition, signaling through short-chain fatty acid-sensitive G protein-coupled receptors, and modulation of pathways related to NF-κB activation. Clinical findings are most promising in ulcerative colitis, especially with microencapsulated formulations. In irritable bowel syndrome, metabolic disorders, and pediatric inflammatory bowel disease, the results remain limited or inconsistent. Summary: Sodium butyrate supplementation appears to be a promising supportive strategy in selected clinical settings, but current evidence does not justify its use as a universally effective intervention. Further well-designed clinical trials are needed to identify optimal indications, dosing regimens, and patient groups most likely to benefit.